2022
DOI: 10.1186/s13148-022-01337-0
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsies based on DNA methylation as biomarkers for the detection and prognosis of lung cancer

Abstract: Lung cancer (LC) is the main cause of cancer-related mortality. Most LC patients are diagnosed in an advanced stage when the symptoms are obvious, and the prognosis is quite poor. Although low-dose computed tomography (LDCT) is a routine clinical examination for early detection of LC, the false-positive rate is over 90%. As one of the intensely studied epigenetic modifications, DNA methylation plays a key role in various diseases, including cancer and other diseases. Hypermethylation in tumor suppressor genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 148 publications
0
13
0
Order By: Relevance
“…A study on the promoter region of yak HIF found that demethylation may be related to the higher expression of HIF in yak tissues than in general cattle [39]. Abnormal DNA methylation has always served as the biomarker of many diseases [40][41][42], such as cancers [43]. As for the genome, the upstream 2000 bp from the transcription start site is generally considered as the promoter region of the gene [25].…”
Section: Discussionmentioning
confidence: 99%
“…A study on the promoter region of yak HIF found that demethylation may be related to the higher expression of HIF in yak tissues than in general cattle [39]. Abnormal DNA methylation has always served as the biomarker of many diseases [40][41][42], such as cancers [43]. As for the genome, the upstream 2000 bp from the transcription start site is generally considered as the promoter region of the gene [25].…”
Section: Discussionmentioning
confidence: 99%
“…Sputum samples have proven to be highly effective in detecting lung cancer progression early [ 143 , 144 ], specifically in active and former smokers. While relatively few studies have investigated DNAm changes occurring in lung cancer using urine, saliva and pleural effusion, they have still demonstrated the utility of using these liquid biopsy samples for early detection, as well as their success in separating lung cancer subtypes [ 145 ]. The majority of DNAm studies use bulk tissue; however, the methylomes of individual cell types differ, as demonstrated by cell-specific gene expression profiles [ 146 ].…”
Section: Emerging Methods For Liquid Biopsy Biomarker Discoverymentioning
confidence: 99%
“…These profiles show remarkable differences even in early cancer stages, with certain methylation markers specific to particular cancers, whereas some are detectable pan-cancer [139,140]. Some markers have notable specificity to lung cancer metastasis [141]; however, the detection of these metastasis markers, and furthermore of recurrence, is a relatively novel and ongoing area of research [141][142][143].…”
Section: Dna Methylation Markersmentioning
confidence: 99%